Realitas Indepedensi Hakim Konstitusi dalam Pengambilan Putusan Berbasis Data Digital - Brandi Stefano Pedo; Muhamad Aldika Adha Wirya; Theo Prapaskah; Sidi Ahyar Wiraguna (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The digital transformation within the constitutional justice ecosystem has shifted the evidentiary paradigm from conventional methods to electronic data-based systems, carrying fundamental implications for the principle of judicial independence. This study aims to analyze the reality of Constitutional Judges' independence amidst the complexity of decision-making reliant on digital data and to identify new forms of threats to judicial autonomy that are technical and psychological in nature. Employing a normative legal research method with a socio-legal approach, this study deconstructs the regulatory construction of digital evidence under the Constitutional Court Law and its derivatives, while evaluating their impact on the judicial deliberation process. The findings reveal that the absence of standardized protocols for digital data authentication and cybersecurity creates a